Vertical greenery as public art in Malaysia - Abu Bakar, Nur Izzah; Mansor, Mazlina; Harun, Nor Zalina (IIUM Press, International Islamic University Malaysia, 2017)
This book is about vertical greenery (VG), public art (PA) and the implementation of VG as PA in the Malaysia. VG is greenery where plants can be grown on, up, or against internal or external walls of buildings or as freestanding structures. PA is a structure or a form that contains an artistic expression, placed in a freely accessible public space for people to view. An urban area is in need of more greenery in its surroundings. One way to increase greenery is by implementing VG. However, its usage must be explored creatively to ensure its survivability in Malaysia. PA, on the other hand is generally used in Malaysia to decorate public spaces and to fill empty urban spaces. This scenario contradicts with the ultimate objective of public art as an artistic expression that can be used by the public. Hence, there is a need to improve the selection and appearance of PA. Most research on VG focuses on environmental and technical aspects whilst the creative methods to approach VG are seldom researched, especially in Malaysia. As such, this problem offers an opportunity to integrate VG with public art in urban spaces. A place with a combination of art and aesthetics with environmental principles would become a new urban art that extend VG’s survivability in the future. The book presents an exploration on the potentials and approach of the implementation of vertical greenery as public art in Malaysian urban context. The objectives are to identify the significance of vertical greenery, public art and the possibilities of vertical greenery’s implementation as public art. As such, the professionals’ and public's perspectives on its implementation as public art are explored and presented. In terms of data, the book presents field inventory of 15 selected reference sites of VG. Professionals’ opinion in the field of VG and PA were asked using semi-structured interview. An online survey was carried out and presented to know the perception of the public.